Pengaruh Jumlah Mata Parut Terhadap Kapasitas Produksi Mesin Pemarut Batang Sagu - Dito Marian; Saparin Saparin; Eka Sari Wijianti; Yudi Setiawan (Jurnal Inovasi Teknologi Terapan, 2026)
Sago is a local food resource with high potential to be developed as an alternative carbohydrate source in Indonesia. One of the critical stages in sago processing is the grating process, which significantly affects production capacity and efficiency. This study aims to analyze the effect of the number of grating teeth on the performance of a sago stem grating machine. Two grating tooth variations, namely 18 × 20 and 20 × 22, were tested using a 7.5 HP gasoline engine. Each variation was tested three times using sago stems weighing 6,000 grams. The observed parameters included grating time, mass of perfectly grated material, imperfect grated material, wasted material, production capacity, and production efficiency. The results showed that the 20 × 22 grating teeth variation produced better performance, with a production capacity of 128.85 kg/h and an efficiency of 94.70%, compared to the 18 × 20 variation with a capacity of 99.65 kg/h and an efficiency of 89.3%. The study concludes that increasing the number of grating teeth significantly improves the performance of the sago stem grating machine.